PEMBELAJARAN MENULIS TEKS BERITA BERDASARKAN KURIKULUM 2013 PADA SISWA KELAS XII AP SMKN 3 PONTIANAK - Sabaria, Sabaria; Syambasril, Syambasril; Syahrani, Agus (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractLearning to write news texts is an important thing to do. This is due to advances in technology and information in today's modern era. Information that is around us can be known by the crowd. One way is to create news. News as a true event of its existence and has happened can be interesting if the data is packed well too. As a writing skill, learning to write news text can be implemented using learning models in Curriculum 2013. This research was conducted in class XII Administration Office SMKN 3 Pontianak. The purpose of research in learning to write this news text is to describe and conclude about the implementation process, obstacles and the results of learning to write news text. The method used in this study is qualitative, that is to describe the results of research using words. The result is the process of writing textual news execution using Problem Based Learning model. The student barriers include the use of punctuation and the application of predefined spellings, as well as the determination of topic and news writing. The result of learning text writing news students quite well. There are three components that have not been well practiced students, namely word selection, application of structure and sentence formation.       Keywords: learning writing, news text, learning model Curriculum 2013.